Selenium improves photosynthesis and induces ultrastructural changes but does not alleviate cadmium-stress damages in tomato plants - Alves, Leticia Rodrigues [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Rossi, Mônica Lanzoni; Martinelli, Adriana Pinheiro; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2020)
The application of Se to plants growing under Cd contamination may become an alternative strategy to minimize Cd damage. However, there is no specific information available regarding whether Se can affect the anatomical structure and photosynthetic rates of plants under Cd stress. To address questions related to Se-protective responses under Cd stress, we evaluated the structural and ultrastructural aspects, photosynthetic rates and growth of tomato cv. Micro-Tom plants. Plants were exposed to 0.5 mM CdCl2 and further supplemented with 1.0 μM of selenite or selenate. The overall results revealed different trends according to the Se source and Cd application. Both Se sources improved growth, photosynthesis, leaf characteristics and middle lamella thickness between mesophyll cells. In contrast, Cd caused decreases in photosynthesis and growth and damage to the ultrastructure of the chloroplast. The number of mitochondria, peroxisomes, starch grains and plastogloboli and the disorganization of the thylakoids and the middle lamella in plants increased in the presence of Cd or Cd + Se. Se plays an important role in plant cultivation under normal conditions. This finding was corroborated by the identification of specific structural changes in Se-treated plants, which could benefit plant development. However, a reversal of Cd stress effects was not observed in the presence of Se.
Keywords: Abiotic stress; Microscopy; Selenate; Selenite; Solanum lycopersicum